Mapping the ethical aspects in end-of-life care for persons with a severe and persistent mental illness: A scoping review of the literature - Moureau, Loïc; Verhofstadt, Monica; Liégeois, Axel (Frontiers in Psychiatry, 2023)
Persons with severe and persistent mental illness (SPMI) make up a vulnerable group within mental healthcare and society. Not only do they suffer from long-term, serious psychiatric disorders; they often also experience considerable problems in their psychosocial functioning. Research has disclosed that the care needs of this target group are complex, and that the life expectancy of these persons is significantly lower than in the general population. Given (1) the lower life expectancy of persons with SPMI, (2) the higher suicide risk related to mental disorders, and (3) the legalization and practice of medical assistance in dying in an increasing number of countries, it is of utmost importance to map the ethical aspects and challenges of end-of-life care needs in persons with SPMI. Therefore, we charted the way end-of-life care is provided for them by means of a scoping review of the scientific literature, with an emphasis on the ethical aspects surrounding it. We explore existing ethical dilemmas; the underlying ethical values, principles and attitudes; and the locus and stakeholders of ethical dialog regarding end-of-life care in persons with SPMI. The results indicate that the four guiding principles of biomedical ethics can well be identified in the literature, and are each addressed in their own specific way: Autonomy in relation to questions regarding the decision-making capacity of persons with SPMI; Justice in relation to access to quality care and the presence of stigma; and Non-maleficence and Beneficence in relation to the ongoing debate regarding the benefits and obstacles in applying palliative care approaches in the context of psychiatry, and the status of the futility-concept therein. Personal virtues and attitudes in care professionals, like compassion, non-abandonment and upholding dignity are key, as care professionals are the main advocates of persons with SPMI, which often lack an extensive social network. Further, we find that the ethical dialog is mainly focused on care professionals and relatives, rather than the persons with SPMI themselves. This is reflected in the existing research that often had the voices of the latter missing. Future research may benefit from the inclusion of persons with SMPI’s first-hand accounts. End-of-life care for persons with SPMI may benefit from identifying and integrating (locally developed) good practices like cross-sectoral education, specific care models, and ethics support.